A high-anti-rutting bridge deck pavement method for urban expressway heavy traffic

CN122880076APending Publication Date: 2026-10-09CHINA CONSTR EIGHT ENG DIV CORP LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611229093.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-13
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]本发明旨在解决现有城市快速路高架桥面采用钢渣沥青混合料时,因重载交通剪切、游离氧化钙水化膨胀及层间水损泛碱相互耦合导致的早期车辙与剥落问题,而提供一种面向城市快速路重载交通的高抗车辙桥面铺装方法,该铺装方法既能消耗固废又能保障桥面的长效耐久性

Benefits of technology

[0060]高粘改性沥青采用TPE(热塑性弹性体)高粘沥青,60℃粘度>50,000Pa·s,软化点≥110℃,-20℃延度>30cm。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122880076A_ABST
    Figure CN122880076A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of bridge deck pavement, and particularly relates to a high-anti-rutting bridge deck pavement method for heavy traffic of urban expressway. The pavement method comprises the following steps: (1) roughening treatment of bridge deck; (2) laying of waterproof layer of bridge deck; (3) pavement structure combination; and (4) construction of waterproof and drainage system of bridge deck pavement structure. The pavement method solves the early rutting and peeling problems caused by the mutual coupling of heavy traffic shearing, free calcium oxide hydration expansion and water damage alkali between layers when the existing urban expressway viaduct adopts steel slag asphalt mixture, and the pavement method can not only consume solid waste but also guarantee the long-term durability of the bridge deck.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of bridge deck paving, specifically relating to a method for high rutting resistance bridge deck paving for heavy traffic on urban expressways. Background Technology

[0002] As key infrastructure for alleviating traffic congestion, urban expressways and elevated bridges endure extremely harsh service environments. Unlike national and provincial highways, urban expressways typically have dedicated bus lanes and freight lanes, resulting in a very high proportion of heavy-load traffic and frequent acceleration and deceleration. This causes the wheel track area on the bridge surface to experience enormous horizontal shear forces and braking thrust. Furthermore, the significant urban heat island effect means that bridge surface temperatures are often higher than ordinary road sections in summer. Under the combined effects of high temperature and heavy load, the asphalt mixture is highly susceptible to flow deformation, leading to a concentrated outbreak of rutting, shoving, and other defects within a short period after opening to traffic.

[0003] While using industrial solid waste steel slag to replace natural aggregates aligns with green building trends, its performance in bridge deck pavement is less than satisfactory. The inherent hydration and expansion characteristics of free calcium oxide (f-CaO) in steel slag aggregates are particularly detrimental in the stress-laden structural layer of bridge decks. Because the compaction degree of bridge deck pavement is typically 1% to 2% lower than that of the roadbed, and is affected by expansion joints and guardrail joints, rainwater easily seeps into the interlayer interface. This seeping water not only weakens the effectiveness of the waterproof bonding layer but also induces hydration reactions in the f-CaO of the steel slag, causing volume expansion. Simultaneously, it triggers efflorescence at the interface between the cement concrete base layer and the pavement layer—that is, water dissolves calcium hydroxide in the base layer, which migrates upwards and crystallizes under the pumping action of traffic loads. This combined effect of physical expansion and chemical erosion leads to a sharp decrease in interlayer adhesion, causing the pavement layer to loosen, bulge, or even delaminate.

[0004] Furthermore, the porous and highly absorbent surface of steel slag leads to excessive absorption of asphalt and tack coat during construction, resulting in insufficient binder film thickness and making it unable to withstand the shear stress generated by heavy traffic. Existing technical solutions often rely solely on increasing the asphalt grade or aggregate hardness to attempt to solve rutting problems, neglecting the chain reaction between heavy loads, water damage, and salt-alkali erosion. When waterproofing fails and efflorescence occurs, the resulting crystallization and expansion further exacerbates the expansion of micro-cracks within the pavement layer, ultimately leading to irreparable structural damage. Currently, there is a lack of a dedicated bridge deck pavement method that can effectively block the water-salt erosion path and possess excellent shear resistance, specifically tailored to the heavy-load characteristics of urban expressways. Summary of the Invention

[0005] This invention aims to solve the problem of early rutting and spalling caused by the coupling of heavy traffic shear, free calcium oxide hydration expansion and interlayer water loss efflorescence when steel slag asphalt mixture is used on the surface of existing urban expressway viaducts. It provides a highly rutting-resistant bridge pavement method for heavy traffic on urban expressways. This pavement method can both consume solid waste and ensure the long-term durability of the bridge surface.

[0006] The technical solution of this invention is as follows: A method for constructing a highly rutting-resistant bridge pavement for heavy traffic on urban expressways includes the following steps: (1) Bridge surface roughening treatment: First, the bridge deck is divided into three roughening treatment areas: the wheel track zone, the transition zone, and the edge zone. Then, shot blasting is used to roughen the bridge deck.

[0007] The specific operation of shot blasting and deburring is as follows: In the wheel track area, corundum shot is used to erode the floating slurry, and ceramic shot (spherical) is used to perform surface micro-densification and strengthening treatment on the exposed aggregate. This removes residual dust and loose particles while simultaneously compacting the micro-cracks on the aggregate surface through the hammering of the shot. The structural depth of the wheel track area is controlled at 1.0mm-1.2mm, and the exposed aggregate rate is controlled at ≥50%, thereby enhancing the anti-rutting anchoring effect. Corundum shot with a Mohs hardness of 9 is used; spherical ceramic shot is also employed.

[0008] Stainless steel shot is used for light roughening in the transition and edge areas; the structural depth of the transition area is controlled at 0.8mm-0.9mm and the exposed aggregate rate is controlled at 30%-40% to enhance stress buffering; the structural depth of the edge area is controlled at 0.4mm-0.6mm and the exposed aggregate rate is controlled at 10%-20%.

[0009] In the wheel track area: the walking speed is controlled at 1.8m / min-2.0m / min, and the coverage is repeated 3 times.

[0010] Transition zone: Walking speed is controlled at 2.8m / min-3.0m / min, and the coverage is repeated 2 times.

[0011] Edge zone: Walking speed controlled at 4.0m / min-4.5m / min, coverage number of times: 1 round.

[0012] Wheel track zone: refers to the area on the bridge deck where the actual rolling frequency of wheels is the highest. It is usually located within 0.5m-0.8m on both sides of the center line of the lane. It is the part that bears the most concentrated traffic load and the greatest shear stress.

[0013] Transition zone: refers to the intermediate area between the wheel track and the edge zone, located within a range of approximately 0.5m-1.0m from the outer side of the wheel track to the base of the guardrail. This area experiences relatively less stress, but it serves as a buffer to transfer stress from the wheel track to the edge zone.

[0014] Edge zone: refers to the area near the edge of the bridge deck, close to the guardrail or curb, usually within 0.3m-0.5m from the base of the guardrail. This area is basically not directly affected by wheel loads and mainly serves to waterproof and seal.

[0015] Secondly, roughening treatment is carried out simultaneously within a range of 0.1m to 0.12m from the base of the high side guardrail. Fixed-point reciprocating shot is used, and the number of coverages is increased to 2 times to ensure the cleanliness and roughness of the interface.

[0016] Finally, after the roughening process is completed, a silane coupling agent is sprayed on for chemical activation.

[0017] (2) Waterproofing layer laying on bridge deck: A reduced-volume permeable layer and a reduced-material sealing layer are laid sequentially from bottom to top to form a waterproof layer on the bridge deck.

[0018] First, a reduced-weight permeable layer is laid on the bridge deck after the roughening treatment by shot blasting in step (1).

[0019] The asphalt application rate for the reduced-volume tack coat is controlled at 0.4 kg / m³. 2 -0.6kg / m 2 .

[0020] The asphalt application rate is based on pure asphalt, for example, in cationic emulsified asphalt, the asphalt content is 60% (0.6 kg / m³). 2 The application rate corresponds to an emulsion application rate of 1 kg / m³. 2 In water-based epoxy asphalt, the asphalt content is 50% (under the same application rate, the application rate of water-based epoxy asphalt is 1.2 kg / m³). 2 ).

[0021] Compared to conventional permeable layers (0.8-1.2 kg / m²), 2 The amount of asphalt applied in this invention is significantly reduced. The design aims to achieve two objectives: firstly, the reduced-volume tack coat and the subsequent reduced-material seal coat form a double-layer waterproofing system. If the tack coat still uses the conventional amount, excessive total asphalt content can easily lead to interlayer slippage; secondly, the reduced-volume tack coat has a high exposed aggregate rate at the shot-blasted interface, and the reduced amount avoids asphalt accumulation. This design, while ensuring effective penetration and sealing, reserves a reasonable amount of asphalt for the upper reduced-material seal coat.

[0022] The binder for the reduced-weight prime layer is either cationic emulsified asphalt or water-based epoxy asphalt; the application rate, calculated based on the emulsion, is 0.67-1.2 kg / m³. 2Cationic emulsified asphalt can be produced using commercially available conventional products.

[0023] Then, a reduced-material seal layer is laid on top of the reduced-volume permeable layer.

[0024] The binder for the reduced-weight seal layer is any one of anionic emulsified asphalt synchronous crushed stone, SBS modified asphalt synchronous crushed stone, or high-viscosity modified asphalt synchronous crushed stone; the synchronous crushed stone is applied in the following manner: the amount of crushed stone applied to the middle of the bridge deck is controlled at 4-5 kg / m². 2 The amount of gravel spread on both sides of the bridge deck is controlled at 2-3 kg / m². 2 .

[0025] Before applying the reduced-material sealing layer, a waterproof plastic membrane should be laid at the initial spraying section, longitudinal joints, and artificial structures to avoid pollution.

[0026] Traditional bridge deck paving only involves a single layer of synchronous crushed stone seal as a waterproofing layer, with an asphalt application rate of 1.2-1.6 kg / m². 2 The crushed stone coverage is approximately 70%. The bridge deck pavement structure has relatively large gaps in practical applications, resulting in exposed asphalt film on the surface. This makes it susceptible to problems such as bleeding and shoving during hot seasons. Details are as follows: 1) The thin thickness of the single-layer asphalt film makes it prone to interlayer displacement in the high shear stress area of ​​the bridge; 2) The 70% coverage of crushed stone means that 30% of the bridge deck area lacks crushed stone interlocking. These blank areas become weak areas where the asphalt is easily softened during the upper asphalt layer paving or in the high-temperature season, thus posing a risk of localized bleeding and deepening rutting in the pavement layer; 3) The single-layer structure cannot effectively cope with the water seepage problem caused by insufficient compaction of the bridge deck. Once rainwater penetrates the asphalt layer, it directly contacts the cement concrete bridge deck, causing water damage and mud pumping. In addition, the water accumulated in the voids of the crushed stone generates expansion stress under freeze-thaw cycles, accelerating the fatigue cracking of the waterproof layer.

[0027] The waterproof layer of this invention innovatively adopts a combination of reduced-volume permeable layer and reduced-material sealing layer. The design of different binder dosages for different layers of the waterproof layer, as well as the design of the amount of crushed stone sprinkled at different locations on the bridge deck for the reduced-material sealing layer, can achieve a reasonable configuration of binder dosage, thereby avoiding problems such as oil seepage caused by excessive spraying or poor waterproofing effect caused by insufficient spraying.

[0028] (3) Pavement structure combination: The modified asphalt mortar layer, the first bonding layer, the lower bridge deck asphalt concrete pavement layer, the second bonding layer, and the upper bridge deck asphalt concrete pavement layer are laid sequentially from bottom to top.

[0029] The coarse aggregate in the modified asphalt mortar layer is hot-quenched steel slag, the fine aggregate is limestone manufactured sand, the filler is limestone mineral powder, and the binder is SBS modified asphalt.

[0030] The coarse aggregate in both the lower and upper asphalt concrete pavement layers is hot-quenched steel slag, the fine aggregate is limestone manufactured sand, the filler is limestone mineral powder, and the binder is SBS modified asphalt.

[0031] To ensure the volume stability and rutting resistance of steel slag in heavy-duty bridge deck applications, this invention features a coordinated design of material specifications and gradation. The hot-quenched steel slag must meet the following requirements: free calcium oxide (f-CaO) content ≤ 3.0%, water immersion expansion rate ≤ 0.8%, and crushing value ≤ 18%, to ensure that it does not undergo hydration expansion leading to efflorescence and spalling under the complex stress environment of the bridge deck.

[0032] The modified asphalt mortar layer acts as a dense waterproof layer, directly sealing micro-cracks in the bridge deck, blocking the path of water infiltration, and preventing the steel slag from contacting the alkaline components of the bridge deck; the lower layer forms the main load-bearing skeleton, utilizing the high hardness of the steel slag to resist heavy-load shearing; the upper layer serves as a wear-resistant layer.

[0033] The first bonding layer uses SBS modified emulsified asphalt, with a spraying rate controlled at 0.5-0.8 kg / m³ (based on emulsion). 2 .

[0034] The second bonding layer uses SBS modified emulsified asphalt, with a spraying rate controlled at 0.5-0.8 kg / m³ (based on emulsion). 2 .

[0035] After the lower asphalt concrete pavement layer is completed, L-shaped asphalt tape is bonded at the joint between this layer and the upper asphalt concrete pavement layer, as well as between the upper asphalt concrete pavement layer and the crash barrier located on the higher side of the bridge deck.

[0036] Before laying L-shaped asphalt tape, the base surface temperature should be greater than 50℃. After laying, the tape should be compacted three times with a rubber-tired roller to ensure that the bonding area ratio is ≥95%.

[0037] (4) Construct a drainage system for the bridge deck pavement structure: The construction of the waterproofing and drainage system is divided into three parts: waterproofing of the bridge deck, waterproofing and drainage of the lower bridge deck asphalt concrete pavement layer, and waterproofing and drainage of the upper bridge deck asphalt concrete pavement layer.

[0038] Bridge deck waterproofing: The waterproof layer at the bottom of the bridge deck is composed of the reduced-volume permeable layer and the reduced-material sealing layer described in step (2). It penetrates and seals the microscopic water seepage channels on the surface of the bridge deck, physically blocking the path of water seepage to the bridge deck, and ensuring that the bridge deck remains dry throughout its entire life cycle. The design slope is a cross slope of 1.5%-2%.

[0039] Drainage and waterproofing of the lower bridge deck asphalt concrete pavement layer: After the mixture of the lower bridge deck asphalt concrete pavement layer is compacted 1-2 times with a rubber-tired roller, emulsified asphalt is applied to the side of the crash barrier on the higher side of the bridge deck cross slope where it meets this layer, and hot-melt tape is then attached. Longitudinal blind drains or drainage channels are installed at the edge area on the lower side of the bridge deck cross slope. The width of the longitudinal blind drains is 10cm-20cm, filled with single-size crushed stone and open-graded asphalt mixture; the width of the drainage channels is 5cm-10cm. The blind drains or drainage channels are connected to the bridge's drainage holes. The top surface of the drainage outlet should be 5-10mm lower than the surrounding bridge deck pavement to ensure that water between seepage layers is promptly discharged through the bridge's drainage holes.

[0040] Waterproofing of the upper bridge deck asphalt concrete pavement layer: After the mixture of the upper bridge deck asphalt concrete pavement layer is laid, emulsified asphalt is applied to the outside of the markings on the high side of the bridge deck cross slope (the side closest to the guardrail) to form a waterproofing system on the high side of the bridge deck cross slope of the pavement structure, ensuring that water upstream of the pavement will not seep in along the joint between the pavement and the guardrail.

[0041] In this invention, the high rutting resistance bridge deck paving method for heavy traffic on urban expressways, when the reduced material seal layer laid in step (2) is anionic emulsified asphalt synchronous crushed stone, the crushed stone adopts a zoned gradation design: 4.75-9.5mm limestone is laid in the wheel track zone; 4.75-7.2mm limestone is laid in the transition zone; and 2.36-4.75mm limestone (pre-wrapped with 0.5% cement) is laid in the edge zone. The crushed stone embedding rate is >70%, forming a barbed structure, and the shear strength is >2.5MPa.

[0042] The asphalt application rate for the reduced-grade seal layer is controlled at 0.4 kg / m³. 2 -0.6kg / m 2 (Based on pure asphalt). Taking anionic emulsified asphalt with an asphalt content of 60% as an example, 0.6 kg / m³ 2 The corresponding emulsion application rate for pure asphalt is 1.0 kg / m³. 2 The asphalt is applied using a multi-stage spraying process: the first application covers 60% of the total amount, forming a film at 60℃; the second application covers the remaining 40%, reinforcing the coating at 90℃, achieving full coverage and zero aggregate shedding. Shear strength > 2.5 MPa.

[0043] In this invention, the high rutting resistance bridge deck paving method for heavy traffic on urban expressways, when the reduced material seal layer laid in step (2) is made of SBS modified asphalt synchronous crushed stone, the crushed stone adopts a compound particle size design: it is composed of 70wt% basalt with a particle size of 5-10mm and 30% limestone with a particle size of 2.36-4.75mm.

[0044] Pre-coating with epoxy resin at 0.6%-0.8% of the total mass of crushed stone, with a crushed stone embedding rate of >80% and a shear strength of >3.0MPa.

[0045] The asphalt application rate for the reduced-grade seal layer is controlled at 0.4 kg / m³. 2 -0.6kg / m 2 (Based on pure asphalt). Asphalt was sprayed at a high temperature of 170±5℃; the crushed stone was applied using a layered covering process, with 70% of the total crushed stone applied in the first layer and the remaining 30% applied in the second layer to ensure uniform interlocking. Measured shear strength > 3.0 MPa.

[0046] In this invention, the high rutting resistance bridge deck paving method for heavy traffic on urban expressways, when the material reduction seal layer laid in step (2) is made of high viscosity modified asphalt synchronous crushed stone, the crushed stone is basalt with a single particle size of 6-10mm (polishing value ≥65).

[0047] The crushed stone is pre-coated with 0.5% silane coupling agent, and the crushed stone embedding rate is >75%. High viscosity modified asphalt (viscosity at 60℃ >50,000 Pa·s) forms a barbed-sealing double layer with the embedded crushed stone, with a shear strength >3.5MPa and a water permeability of 0mL / min.

[0048] The asphalt application rate for the reduced-grade seal layer is controlled at 0.4 kg / m³. 2 -0.6kg / m 2 (Based on pure asphalt). Measured shear strength > 3.5 MPa, water permeability 0 mL / min.

[0049] In this invention, the high rutting-resistant bridge deck paving method for heavy traffic on urban expressways, in step (3), the asphalt content in the modified asphalt mortar layer is 6.5%-7.0%; the gradation range of the modified asphalt mortar layer is as follows: 9.5mm sieve pass rate is 100% (volume percentage), 4.75mm sieve pass rate is 90%-100%, 2.36mm sieve pass rate is 28%-50%, 1.18mm sieve pass rate is 20%-36%, 0.6mm sieve pass rate is 18%-26%, 0.3mm sieve pass rate is 15%-22%, 0.15mm sieve pass rate is 12%-18%, and 0.075mm sieve pass rate is 8%-13%.

[0050] The designed modified asphalt mortar layer gradation improvement has a coarse aggregate skeleton with a 4.75mm sieve pass rate of 90-100%, forming a dense skeleton of fine aggregate / mortar interlocking; the fine aggregate is designed with a biased gap, with a 1.18mm sieve pass rate of 20-36%, to avoid fine material filling the gaps in the skeleton.

[0051] In this invention, the high rutting-resistant bridge deck pavement method for heavy traffic on urban expressways has the following gradation ranges for the lower and upper asphalt concrete pavement layer mixtures in step (3): The asphalt content in the lower bridge deck asphalt concrete pavement mixture is 5.6%-5.8%; the passing rate of this mixture through a 19mm sieve is 100% (volume percentage), through a 16mm sieve is 90-100%, through a 13.2mm sieve is 70%-85%, through a 9.5mm sieve is 50%-70%, through a 4.75mm sieve is 22%-35%, through a 2.36mm sieve is 17%-26%, through a 1.18mm sieve is 16%-24%, through a 0.6mm sieve is 14%-20%, through a 0.3mm sieve is 12%-17%, through a 0.15mm sieve is 12%-16%, and through a 0.075mm sieve is 10%-12%.

[0052] The asphalt content in the upper bridge deck asphalt concrete pavement mixture is 5.6%-5.8%. The passing percentage of this mixture through a 19mm sieve is 100% (volume percentage), 90-100% through a 16mm sieve, 65%-85% through a 13.2mm sieve, 45%-65% through a 9.5mm sieve, 20%-32% through a 4.75mm sieve, 15%-24% through a 2.36mm sieve, 14%-22% through a 1.18mm sieve, 12%-18% through a 0.6mm sieve, 10%-15% through a 0.3mm sieve, 9%-14% through a 0.15mm sieve, and 8%-12% through a 0.075mm sieve. This gradation is suitable for road sections with extremely high heavy loads and high requirements for rutting resistance.

[0053] In this invention, the high rutting-resistant bridge deck pavement method for heavy traffic on urban expressways has the following gradation ranges for the lower and upper asphalt concrete pavement layer mixtures in step (3): The asphalt content in the lower bridge deck asphalt concrete pavement mixture is 5.9%-6.1%; the passing rate of this mixture through a 19mm sieve is 100% (volume percentage), the passing rate through a 16mm sieve is 100%, the passing rate through a 13.2mm sieve is 90%-100%, the passing rate through a 9.5mm sieve is 55%-75%, the passing rate through a 4.75mm sieve is 22%-35%, the passing rate through a 2.36mm sieve is 18%-28%, the passing rate through a 1.18mm sieve is 16%-26%, the passing rate through a 0.6mm sieve is 14%-22%, the passing rate through a 0.3mm sieve is 12%-18%, the passing rate through a 0.15mm sieve is 12%-17%, and the passing rate through a 0.075mm sieve is 10%-12%.

[0054] The asphalt content in the upper bridge deck asphalt concrete pavement mixture is 5.9%-6.1%. The mixture has the following pass rates: 100% (volume percentage) through a 19mm sieve, 100% through a 16mm sieve, 90%-100% through a 13.2mm sieve, 50%-75% through a 9.5mm sieve, 20%-34% through a 4.75mm sieve, 15%-26% through a 2.36mm sieve, 14%-24% through a 1.18mm sieve, 12%-20% through a 0.6mm sieve, 10%-16% through a 0.3mm sieve, 9%-15% through a 0.15mm sieve, and 8%-12% through a 0.075mm sieve. This gradation is suitable for road sections with a high proportion of heavy loads, while also considering rutting resistance and fatigue durability.

[0055] The asphalt concrete pavement mixture gradation of the upper and lower bridge deck layers described in this invention ensures that the permeability requirements are met while also taking into account high and low temperature performance and water stability. When designing the target mix proportion and production mix proportion for the lower bridge deck asphalt concrete pavement layer, the gradation range is slightly finer than that of the lower bridge deck section, thereby reducing the segregation phenomenon of coarse aggregate aggregation and ensuring no abnormal permeability.

[0056] This invention constructs a bottom-up, multi-layered waterproofing system in the pavement structure design: First, a reduced-volume tack coat and a subsequent reduced-material seal coat form a double-layer waterproofing system, together constituting the first layer of waterproofing; second, the asphalt sand layer adopts a dense-grained mortar gradation with extremely low porosity, forming the second layer of waterproofing; finally, the upper and lower layer mixtures also adopt a low-porosity design, resulting in high overall density after compaction, forming the third layer of waterproofing. These three layers, stacked and working together, prevent water from seeping down the pavement, achieving full-section waterproofing from the base layer to the surface layer, fundamentally solving the problem of water seepage in bridge deck pavement.

[0057] In this invention, the high rutting resistance bridge pavement method for heavy traffic on urban expressways, in step (2), is a water-based epoxy asphalt compounded from epoxy resin emulsion and anionic emulsified asphalt at a mass ratio of 1:0.8. 2% silane coupling agent is added during construction. After demulsification, the epoxy resin completely encapsulates the asphalt components, exhibiting a tensile strength > 5 MPa, elongation ≥ 300%, and interfacial bond strength ≥ 2.2 MPa.

[0058] Preferably, the anionic emulsified asphalt is sodium dodecyl sulfonate anionic emulsified asphalt. This emulsified asphalt contains 5% SBR latex and 3% nano-clay, forming a stable emulsion with a Zeta potential of approximately -45mV.

[0059] In this invention, the high rutting resistance bridge pavement method for heavy traffic on urban expressways, in step (2), the SBS modified asphalt uses 70# or 90# road petroleum asphalt as the matrix, and adds 4.2%-4.5% by mass of star-shaped SBS modifier for shear modification. In the modification process, 2% by mass of natural rock asphalt and 0.3% by mass of sulfur are added as auxiliary modifiers, the softening point reaches above 85℃, and the elastic recovery rate reaches above 95%.

[0060] The high-viscosity modified asphalt uses TPE (thermoplastic elastomer) high-viscosity asphalt with a viscosity of >50,000 Pa·s at 60℃, a softening point of ≥110℃, and a ductility of >30 cm at -20℃.

[0061] The beneficial effects of this invention are as follows: In the high-rutting-resistant bridge deck pavement method for heavy traffic on urban expressways described in this invention, the waterproof layer first adopts a combination design of a reduced-volume permeable layer and a reduced-material seal layer. This design, on the one hand, reduces asphalt usage by matching the adsorption characteristics of the shot-blasted roughened interface with the reduced-volume permeable layer, avoiding asphalt accumulation and achieving precise penetration and sealing on demand. On the other hand, the total asphalt content remains within a reasonable range after the reduced-volume permeable layer and the reduced-material seal layer are stacked, avoiding the risk of excessive asphalt usage in traditional single permeable layers, which can easily lead to interlayer shifting after being superimposed with the subsequent seal layer. Furthermore, the double-layer structure forms a three-dimensional waterproof barrier. This combined design effectively controls the total asphalt usage while ensuring waterproofing performance, reducing material costs, and fundamentally solving common quality problems in traditional bridge deck pavement caused by interlayer asphalt accumulation, such as high-temperature shifting and bleeding, achieving a synergistic improvement in waterproofing performance and structural stability.

[0062] The upper and lower asphalt concrete pavement layers and the modified asphalt mortar layer of the bridge deck are all designed as discontinuously graded, dense-grained asphalt mixtures. This design fully utilizes the coarse texture and angularity of hot-melted steel slag aggregate. Through the discontinuous design, a stone-to-stone contact skeleton is formed between the coarse aggregate steel slag, significantly increasing the internal friction angle, thereby giving the bridge deck extremely strong resistance to heavy-load shearing and rutting deformation. At the same time, by utilizing the high hardness and rigidity of steel slag, the overall load-bearing capacity is improved while ensuring that the pavement layer maintains excellent smoothness under long-term heavy-load compaction.

[0063] The paving method described in this invention starts with the roughening treatment of the bridge deck by shot blasting, then proceeds through the penetration of the reduced-volume permeable layer, the waterproofing and stress absorption of the reduced-material sealing layer, to the leveling, bonding and waterproofing of the asphalt sand, then to the construction of the improved lower layer and the asphalt tape, and finally to the construction of the upper layer. The whole series of processes forms a gradient waterproofing, which effectively prevents the entry of external water and avoids the phenomenon of whitening and efflorescence on the bridge deck. Attached Figure Description

[0064] Figure 1 This is a photo of the bridge surface showing signs of efflorescence.

[0065] Figure 2 This is an image showing the effect of roughening the bottom of the guardrail in the paving method described in this invention.

[0066] Figure 3 This is a diagram showing the bridge surface after the wheel track belt in the paving method described in this invention has been roughened by shot blasting.

[0067] Figure 4 This is a diagram showing the bridge deck surface after shot blasting roughening treatment of the transition zone in the paving method described in this invention.

[0068] Figure 5 This is a diagram showing the bridge deck surface after the edge area of ​​the paving method described in this invention has been roughened by shot blasting.

[0069] Figure 6 This is an illustration of the effect of the reduced-volume permeable layer and reduced-material sealing layer laid in the paving method described in this invention.

[0070] Figure 7 This is an image showing the effect of asphalt paving in the paving method described in this invention. Detailed Implementation

[0071] The technical solution of the present invention will be described in detail below.

[0072] Example 1 The specific steps of the high-rutting-resistance bridge pavement method for heavy traffic on urban expressways are as follows: (1) Bridge surface roughening treatment: First, the bridge deck is divided into three roughening areas: the wheel track zone, the transition zone, and the edge zone.

[0073] Then, roughening treatment is performed by shot blasting, and the specific operation is as follows: In the wheel track area, diamond shot with a Mohs hardness of 9 was used to erode the floating slurry, and ceramic shot was used to perform surface micro-densification strengthening treatment on the exposed aggregate. While removing residual dust and loose particles, the hammering of the shot compacted the micro-cracks on the surface of the aggregate. The structural depth of the wheel track area was controlled at 1.1 mm, and the exposed aggregate rate was controlled at 55%.

[0074] Stainless steel shot is used for light roughening in the transition and edge areas; the structural depth of the transition area is controlled at 0.85 mm and the exposed aggregate rate is controlled at 35% to enhance stress buffering; the structural depth of the edge area is controlled at 0.5 mm and the exposed aggregate rate is controlled at 15%.

[0075] The number of shots and the speed at which shot blasting was performed in each area are shown in Table 1.

[0076] Table 1

[0077] Secondly, roughening treatment is carried out simultaneously within a range of 0.1m to 0.12m from the base of the high side guardrail, using fixed-point reciprocating shot blasting, with the number of coverages increased to 2.

[0078] Finally, after the roughening treatment is complete, a silane coupling agent is sprayed for chemical activation, forming a CaSiO3·nH2O active film on the surface of the roughened area. The spraying amount of the silane coupling agent is 200 g / m². 2 .

[0079] (2) Laying of waterproof layer on bridge deck The bridge deck is waterproofed by laying a reduced-volume permeable layer and a reduced-material seal layer sequentially from bottom to top. Before applying the reduced-material seal layer, a waterproof plastic membrane should be laid at the initial application section, longitudinal joints, and artificial structures to prevent contamination.

[0080] The asphalt application rate for the reduced-volume tack coat is 0.5 kg / m³. 2 (Based on pure asphalt), cationic emulsified asphalt is used, with an asphalt content of 60%, corresponding to an emulsion application rate of 0.83 kg / m³. 2 .

[0081] The asphalt application rate of the reduced-material seal layer is 0.6 kg / m² (based on pure asphalt). It uses anionic emulsified asphalt synchronous crushed stone, and the anionic emulsified asphalt is sodium dodecyl sulfonate anionic emulsified asphalt. 5 wt% SBR latex and 3 wt% nano clay are added to form a stable emulsion with a Zeta potential of about -45 mV.

[0082] The asphalt is applied using a multi-stage spraying process: the first spraying applies 60% of the total amount (0.36 kg / m²), which forms a film at 60°C; the second spraying applies the remaining 40% (0.24 kg / m²), which is then applied at 90°C for enhanced coating, achieving full coverage and zero stone detachment.

[0083] The wheel track zone (the central area of ​​the bridge deck) is paved with 4.75-9.5mm limestone at a spreading rate of 4.5kg / m²; the transition zone (between the wheel track zone and the edge zone) is paved with 4.75-7.2mm limestone at a spreading rate of 3.0kg / m²; the edge zone (the areas near the guardrails on both sides of the bridge deck) is paved with 2.36-4.75mm limestone at a spreading rate of 2.5kg / m², with a crushed stone embedding rate >70%, forming a barbed structure. The measured shear strength, according to JTGE20 standard, is 2.9MPa.

[0084] (3) Pavement structure combination The modified asphalt mortar layer, the first bonding layer, the lower bridge deck asphalt concrete pavement layer, the second bonding layer, and the upper bridge deck asphalt concrete pavement layer are laid sequentially from bottom to top.

[0085] The modified asphalt mortar layer uses an asphalt mortar mixture, with hot-cured steel slag as coarse aggregate, manufactured limestone sand as fine aggregate, limestone mineral powder as filler, and SBS modified asphalt as binder; the asphalt content is 6.8%, and no fibers are added. The compacted thickness is 20mm.

[0086] The free calcium oxide (f-CaO) content in the hot-quenched steel slag is ≤3.0%, the water immersion expansion rate is ≤0.8%, and the crushing value is ≤18%.

[0087] The gradation range of the modified asphalt mortar layer is as follows: 100% passing through a 9.5mm sieve, 98.5% passing through a 4.75mm sieve, 40.1% passing through a 2.36mm sieve, 28.3% passing through a 1.18mm sieve, 22.6% passing through a 0.6mm sieve, 18.5% passing through a 0.3mm sieve, 15.2% passing through a 0.15mm sieve, and 10.4% passing through a 0.075mm sieve.

[0088] The first bonding layer uses SBS modified emulsified asphalt, with a spraying rate of 0.5 kg / m³ (based on emulsion). 2 .

[0089] The coarse aggregate of the lower bridge deck asphalt concrete pavement mixture is hot-cured steel slag, the fine aggregate is limestone manufactured sand, the filler is limestone mineral powder, the binder is SBS modified asphalt, and the compaction thickness is 40mm.

[0090] The lower bridge deck asphalt concrete pavement layer has an asphalt content of 5.8%. The mixture gradation is as follows: 100% passing through a 19mm sieve, 95.2% passing through a 16mm sieve, 78.6% passing through a 13.2mm sieve, 60.4% passing through a 9.5mm sieve, 28.5% passing through a 4.75mm sieve, 22.2% passing through a 2.36mm sieve, 20.3% passing through a 1.18mm sieve, 17.5% passing through a 0.6mm sieve, 15.6% passing through a 0.3mm sieve, 14.4% passing through a 0.15mm sieve, and 11.2% passing through a 0.075mm sieve.

[0091] The second bonding layer uses SBS modified emulsified asphalt, applied at a rate of 0.5 kg / m³ (based on emulsion). 2 .

[0092] The coarse aggregate of the upper bridge deck asphalt concrete pavement mixture is hot-cured steel slag, the fine aggregate is limestone manufactured sand, the filler is limestone mineral powder, the binder is SBS modified asphalt, and the compaction thickness is 40mm.

[0093] The upper asphalt concrete pavement layer of the bridge deck has an asphalt content of 5.8%. The mixture gradation is as follows: 100% passing through a 19mm sieve, 100% passing through a 16mm sieve, 85% passing through a 13.2mm sieve, 55.2% passing through a 9.5mm sieve, 26.6% passing through a 4.75mm sieve, 20.7% passing through a 2.36mm sieve, 18.3% passing through a 1.18mm sieve, 15.2% passing through a 0.6mm sieve, 12.6% passing through a 0.3mm sieve, 11.4% passing through a 0.15mm sieve, and 10.2% passing through a 0.075mm sieve.

[0094] After the lower asphalt concrete pavement layer is completed, L-shaped asphalt tape is bonded at the joints between it and the upper asphalt concrete pavement layer, and between the upper asphalt concrete pavement layer and the guardrail located on the higher side of the bridge deck. The L-shaped asphalt tape is 30cm wide and 3mm thick. The substrate temperature must be greater than 50℃ before application. After application, the surface is compacted three times with a rubber-tired roller to ensure a bonding area ratio of ≥95%.

[0095] (4) Construction of drainage system The waterproofing and drainage system is constructed in three parts: waterproofing of the bridge deck, waterproofing and drainage of the lower bridge deck asphalt concrete pavement layer, and waterproofing and drainage of the upper bridge deck asphalt concrete pavement layer.

[0096] Bridge deck waterproofing: designed with a cross slope of 1.8%. The reduced-volume permeable layer and the reduced-material seal layer together constitute the waterproofing layer at the bottom of the bridge deck.

[0097] Drainage and waterproofing of the lower bridge deck asphalt concrete pavement layer: After the lower bridge deck asphalt concrete pavement mixture is compacted twice with a rubber-tired roller, emulsified asphalt is applied to the side of the crash barrier on the higher side of the bridge deck's cross slope where it connects to this layer, and hot-melt tape is then attached. Longitudinal blind drains or drainage channels are installed at the edge area on the lower side of the bridge deck's cross slope. The longitudinal blind drains are 15cm wide and filled with single-size crushed stone and open-graded asphalt mixture; the drainage channels are 6cm wide. The blind drains or drainage channels are connected to the bridge's drainage holes. The top surface of the drainage outlets should be 6mm lower than the surrounding bridge deck pavement to ensure that water between seepage layers is promptly discharged through the bridge's drainage holes.

[0098] The compaction of asphalt pavement layers adopts a combination process of vibratory steel wheel roller and rubber-tired roller: firstly, the vibratory steel wheel roller is used for main compaction, rolling 4 to 6 times until the compaction degree meets the requirements; then, the rubber-tired roller is used for kneading and compaction 2 times to seal the surface pores.

[0099] Example 2 The difference between this embodiment and Embodiment 1 lies in the following steps: (2) Laying of waterproof layer on bridge deck The reduced-weight seal layer uses SBS modified asphalt synchronous crushed stone, which is designed with a composite particle size: it is composed of 70 wt% basalt with a particle size of 5-10 mm and 30% limestone with a particle size of 2.36-4.75 mm.

[0100] Pre-coating with epoxy resin at 0.6% of the total mass of crushed stone results in a crushed stone embedding rate >80%. The asphalt application rate for the reduced-material seal layer is controlled at 0.5 kg / m² (based on pure asphalt). The asphalt is applied at a high temperature of 165°C; the crushed stone is covered using a layered process, with 70% of the total crushed stone applied in the first layer and the remaining 30% applied in the second layer to ensure uniform embedding.

[0101] (3) Pavement structure combination The modified asphalt mortar layer contains 7.0% asphalt. The mixture gradation is as follows: 100% passing through a 9.5mm sieve, 98.3% passing through a 4.75mm sieve, 45.5% passing through a 2.36mm sieve, 34.2% passing through a 1.18mm sieve, 25.1% passing through a 0.6mm sieve, 21.6% passing through a 0.3mm sieve, 17.2% passing through a 0.15mm sieve, and 13% passing through a 0.075mm sieve.

[0102] The lower bridge deck asphalt concrete pavement layer has an asphalt content of 5.7%. The mixture gradation is as follows: 100% passing through a 19mm sieve, 100% passing through a 16mm sieve, 85% passing through a 13.2mm sieve, 60.4% passing through a 9.5mm sieve, 27.5% passing through a 4.75mm sieve, 25.2% passing through a 2.36mm sieve, 22.5% passing through a 1.18mm sieve, 17.5% passing through a 0.6mm sieve, 15.6% passing through a 0.3mm sieve, 14.1% passing through a 0.15mm sieve, and 11.5% passing through a 0.075mm sieve.

[0103] The upper bridge deck asphalt concrete pavement layer has an asphalt content of 5.8%. The mixture gradation is as follows: 100% passing through a 19mm sieve, 100% passing through a 16mm sieve, 85% passing through a 13.2mm sieve, 60.5% passing through a 9.5mm sieve, 27.5% passing through a 4.75mm sieve, 23.7% passing through a 2.36mm sieve, 18.2% passing through a 1.18mm sieve, 16.8% passing through a 0.6mm sieve, 15% passing through a 0.3mm sieve, 12.5% ​​passing through a 0.15mm sieve, and 11.1% passing through a 0.075mm sieve.

[0104] Example 3 The difference between this embodiment and Embodiment 1 lies in the following steps: (2) Laying of waterproof layer on bridge deck The reduced-weight seal layer uses high-viscosity modified asphalt synchronous crushed stone. The crushed stone is basalt with a single particle size of 6-10mm (polished value ≥65), and is pre-coated with 0.5% silane coupling agent, with a crushed stone embedding rate >75%. The high-viscosity modified asphalt is commercially available TPE high-viscosity modified asphalt, which forms a barbed-sealing dual-effect layer with the embedded crushed stone, and the water permeability rate is 0mL / min.

[0105] The hot-quenched steel slag has a free calcium oxide (f-CaO) content of ≤3.0%, a water immersion expansion rate of ≤0.8%, and a crushing value of ≤18%.

[0106] Modified asphalt mortar layer: asphalt content 6.8%. The mixture gradation is as follows: 100% passing through a 9.5mm sieve, 95.2% passing through a 4.75mm sieve, 39.1% passing through a 2.36mm sieve, 28.6% passing through a 1.18mm sieve, 22.7% passing through a 0.6mm sieve, 18.3% passing through a 0.3mm sieve, 15.9% passing through a 0.15mm sieve, and 10.2% passing through a 0.075mm sieve.

[0107] The lower bridge deck asphalt concrete pavement layer contains 5.9% asphalt. The mixture gradation is as follows: 100% passing through a 19mm sieve, 100% passing through a 16mm sieve, 95.2% passing through a 13.2mm sieve, 70.7% passing through a 9.5mm sieve, 28.2% passing through a 4.75mm sieve, 21.4% passing through a 2.36mm sieve, 20.5% passing through a 1.18mm sieve, 17.6% passing through a 0.6mm sieve, 14.3% passing through a 0.3mm sieve, 14.5% passing through a 0.15mm sieve, and 11.2% passing through a 0.075mm sieve.

[0108] Upper bridge deck asphalt concrete pavement: Asphalt content 6.0%. The mixture gradation is as follows: 100% passing through a 19mm sieve, 100% passing through a 16mm sieve, 95.5% passing through a 13.2mm sieve, 64.2% passing through a 9.5mm sieve, 26.7% passing through a 4.75mm sieve, 21.6% passing through a 2.36mm sieve, 19.2% passing through a 1.18mm sieve, 15.5% passing through a 0.6mm sieve, 12.4% passing through a 0.3mm sieve, 11.3% passing through a 0.15mm sieve, and 10.6% passing through a 0.075mm sieve.

[0109] Example 4 The difference between this embodiment and Embodiment 1 lies in the following steps: (3) Pavement structure combination The hot-quenched steel slag must meet the following requirements: free calcium oxide (f-CaO) content ≤ 3.0%, water immersion expansion rate ≤ 0.8%, and crushing value ≤ 18%.

[0110] Modified asphalt mortar layer: asphalt content 6.7%. The mixture gradation is as follows: 100% passing through a 9.5mm sieve, 95.2% passing through a 4.75mm sieve, 35.7% passing through a 2.36mm sieve, 26.6% passing through a 1.18mm sieve, 22.4% passing through a 0.6mm sieve, 18.5% passing through a 0.3mm sieve, 15.3% passing through a 0.15mm sieve, and 12.5% ​​passing through a 0.075mm sieve.

[0111] The lower bridge deck asphalt concrete pavement layer has an asphalt content of 5.8%. The mixture gradation is as follows: 100% passing through a 19mm sieve, 100% passing through a 16mm sieve, 85% passing through a 13.2mm sieve, 61.2% passing through a 9.5mm sieve, 27.0% passing through a 4.75mm sieve, 25.6% passing through a 2.36mm sieve, 20.3% passing through a 1.18mm sieve, 18.5% passing through a 0.6mm sieve, 15.6% passing through a 0.3mm sieve, 14.2% passing through a 0.15mm sieve, and 11.4% passing through a 0.075mm sieve.

[0112] Upper bridge deck asphalt concrete pavement: asphalt content 5.8%. The mixture gradation is as follows: 100% passing through a 19mm sieve, 100% passing through a 16mm sieve, 85% passing through a 13.2mm sieve, 61.5% passing through a 9.5mm sieve, 27.2% passing through a 4.75mm sieve, 23.1% passing through a 2.36mm sieve, 19.5% passing through a 1.18mm sieve, 16.4% passing through a 0.6mm sieve, 13.9% passing through a 0.3mm sieve, 12.3% passing through a 0.15mm sieve, and 10.7% passing through a 0.075mm sieve.

[0113] Comparative Example 1 The difference between this comparative example and Example 1 is that the amount of reduced tack coat asphalt applied is the conventional amount of 1.0 kg / m² (based on pure asphalt), and the amount of reduced seal coat asphalt applied is the conventional amount of 1.5 kg / m² (based on pure asphalt).

[0114] All other materials and construction techniques are the same as in Example 1.

[0115] Comparative Example 2 The difference between this comparative example and Example 1 is that the crushed stone used in step (2) for the material reduction sealing layer is basalt with a single particle size of 5-10mm, and the amount of spraying is controlled according to the full coverage of 90% of the area. No zoning gradation design or pre-coating treatment is used.

[0116] Comparative Example 3 The difference between this comparative example and Example 1 is that the modified asphalt mortar layer in step (3) adopts conventional AC-5 gradation, with an asphalt content of 6.7% and the following gradation: 9.5mm sieve pass rate 100%, 4.75mm sieve pass rate 98.9%, 2.36mm sieve pass rate 59.4%, 1.18mm sieve pass rate 38.0%, 0.6mm sieve pass rate 23.3%, 0.3mm sieve pass rate 13.0%, 0.15mm sieve pass rate 10.1%, and 0.075mm sieve pass rate 8.6%.

[0117] Comparative Example 4 This comparative example uses a traditional bridge deck pavement structure, and differs from Example 1 in that: (1) Only one ordinary permeable layer is set, without material reduction sealing layer; no modified asphalt mortar layer; only one adhesive layer is set between the upper and lower layers, without L-shaped asphalt waterproofing treatment.

[0118] (2) Conventional shot blasting was used to roughen the surface of the bridge, and the entire bridge surface was uniformly treated with a structural depth of 0.5mm-0.7mm and an exposed aggregate rate of 20%-25%. No zoning design was carried out.

[0119] (3) The tack coat uses ordinary cationic emulsified asphalt, with a spraying amount of 1.0 kg / m² (based on pure asphalt), and is completed in one spraying. No multi-spraying process is used.

[0120] (4) The lower bridge deck asphalt concrete pavement layer uses steel slag AC-20C asphalt mixture with an asphalt content of 4.2% and a traditional continuous gradation: 19mm sieve pass rate 94.4%, 16mm sieve pass rate 80.9%, 13.2mm sieve pass rate 70.6%, 9.5mm sieve pass rate 60.9%, 4.75mm sieve pass rate 39.9%, 2.36mm sieve pass rate 23.4%, 1.18mm sieve pass rate 16.6%, 0.6mm sieve pass rate 11.8%, 0.3mm sieve pass rate 8.0%, 0.15mm sieve pass rate 6.9%, and 0.075mm sieve pass rate 5.3%.

[0121] (5) The asphalt concrete of the upper bridge deck is made of steel slag SMA-13 ​​asphalt mixture with an asphalt content of 5.6% and a traditional continuous gradation: 100% pass rate of 16mm sieve, 92.3% pass rate of 13.2mm sieve, 65.2% pass rate of 9.5mm sieve, 30.0% pass rate of 4.75mm sieve, 21.5% pass rate of 2.36mm sieve, 17.2% pass rate of 1.18mm sieve, 14.7% pass rate of 0.6mm sieve, 13.0% pass rate of 0.3mm sieve, 12.0% pass rate of 0.15mm sieve, and 10.3% pass rate of 0.075mm sieve.

[0122] Comparative Example 5 The difference between this comparative example and Example 1 is that the bridge deck was not subjected to zonal roughening treatment, and the entire bridge deck was subjected to uniform shot blasting using the same process and parameters.

[0123] The entire bridge surface is treated with stainless steel shot, with a walking speed of 3.5m / min, and is covered twice.

[0124] Post-treatment testing showed that the structural depth of the entire bridge deck was uniformly controlled at 0.6 mm, and the exposed aggregate rate was controlled at 25%.

[0125] All other materials and construction techniques (waterproofing layer, paving layer, drainage system) are the same as in Example 1.

[0126] The performance indicators of the bridge deck pavement structure obtained through the various embodiments and comparative paving methods are shown in Table 2.

[0127] Table 2

[0128] It is evident that the paving method described in this invention can both consume solid waste and ensure the long-term durability of the bridge deck.

Claims

1. A method for constructing a highly rutting-resistant bridge pavement for heavy traffic on urban expressways, characterized in that, Includes the following steps: (1) Bridge surface roughening treatment: First, the bridge deck is divided into three roughening treatment areas: the wheel track zone, the transition zone, and the edge zone. Then, shot blasting is used to roughen the bridge deck. The specific operation of shot blasting and deburring is as follows: In the wheel track zone area, diamond shot was used to erode the floating slurry, and ceramic shot was used to perform surface micro-densification strengthening treatment on the exposed aggregate; the structural depth of the wheel track zone area was controlled at 1.0mm-1.2mm, and the exposed aggregate rate was controlled at ≥50%; In the transition and edge areas, stainless steel shot is used for light roughening treatment; The structural depth of the transition zone is controlled at 0.8mm-0.9mm, and the exposed bone rate is controlled at 30%-40%. The construction depth of the edge zone is controlled at 0.4mm-0.6mm, and the exposed bone rate is controlled at 10%-20%. In the wheel track area: the walking speed is controlled at 1.8m / min-2.0m / min, and the coverage is repeated 3 times; Transition zone: Walking speed controlled at 2.8m / min-3.0m / min, covering twice; Edge zone: Walking speed controlled at 4.0m / min-4.5m / min, covering once; Secondly, roughening treatment is carried out simultaneously within a range of 0.1m-0.12m at the base of the high side guardrail, using fixed-point reciprocating shot blasting, with the number of coverages increased to 2. Finally, after the roughening process is completed, a silane coupling agent is sprayed on for chemical activation. (2) Waterproofing layer laying on bridge deck: A reduced-volume permeable layer and a reduced-material sealing layer are laid sequentially from bottom to top to form a waterproof layer on the bridge deck; First, a reduced-weight permeable layer is laid on the bridge deck after the roughening treatment by shot blasting in step (1); The asphalt application rate for the reduced-volume tack coat is controlled at 0.4 kg / m³. 2 -0.6kg / m 2 ; The binder for the reduced-weight prime layer is either cationic emulsified asphalt or water-based epoxy asphalt; the application rate, calculated based on the emulsion, is 0.67-1.2 kg / m³. 2 ; Then, a reduced-material seal layer is laid on top of the reduced-volume tack coat; The binder of the reduced-material seal layer is any one of anionic emulsified asphalt synchronous crushed stone, SBS modified asphalt synchronous crushed stone, or high-viscosity modified asphalt synchronous crushed stone. The method for synchronous crushed stone application is as follows: the amount of crushed stone applied to the middle of the bridge deck is controlled at 4-5 kg / m². 2 The amount of gravel spread on both sides of the bridge deck is controlled at 2-3 kg / m². 2 ; (3) Pavement structure combination: The modified asphalt mortar layer, the first bonding layer, the lower bridge deck asphalt concrete pavement layer, the second bonding layer, and the upper bridge deck asphalt concrete pavement layer are laid sequentially from bottom to top. The coarse aggregate in the modified asphalt mortar layer is hot-quenched steel slag, the fine aggregate is limestone manufactured sand, the filler is limestone mineral powder, and the binder is SBS modified asphalt. The coarse aggregate in both the lower and upper asphalt concrete pavement mixtures is hot-quenched steel slag, the fine aggregate is limestone manufactured sand, the filler is limestone mineral powder, and the binder is SBS modified asphalt. The hot-quenched steel slag has a free calcium oxide content of ≤3.0%, a water immersion expansion rate of ≤0.8%, and a crushing value of ≤18%. The first bonding layer uses SBS modified emulsified asphalt, with a spraying rate controlled at 0.5-0.8 kg / m³ (based on emulsion). 2 ; The second bonding layer uses SBS modified emulsified asphalt, with a spraying rate controlled at 0.5-0.8 kg / m³ (based on emulsion). 2 ; After the lower asphalt concrete pavement layer is completed, L-shaped asphalt tape is bonded at the joint between this layer and the upper asphalt concrete pavement layer, as well as between the upper asphalt concrete pavement layer and the crash barrier located on the high side of the bridge deck. (4) Construct a drainage system for the bridge deck pavement structure: The construction of the waterproofing and drainage system is divided into three parts: waterproofing of the bridge deck, waterproofing and drainage of the lower bridge deck asphalt concrete pavement layer, and waterproofing and drainage of the upper bridge deck asphalt concrete pavement layer. Bridge deck waterproofing: The waterproofing layer at the bottom of the bridge deck is composed of the reduced permeable layer and the reduced material sealing layer described in step (2); the design slope is a cross slope of 1.5%-2%; Drainage and waterproofing of the lower bridge deck asphalt concrete pavement layer: After the mixture of the lower bridge deck asphalt concrete pavement layer is compacted 1-2 times with a rubber-tired roller, emulsified asphalt is applied to the side of the crash barrier on the high side of the bridge deck cross slope where it meets this layer, and hot-melt tape is attached; longitudinal blind drains or drainage channels are set in the edge area on the low side of the bridge deck cross slope; the width of the longitudinal blind drain is 10cm-20cm; the width of the drainage channel is 5cm-10cm; Waterproofing and drainage of the upper bridge deck asphalt concrete pavement layer: After the mixture of the upper bridge deck asphalt concrete pavement layer is laid, emulsified asphalt is applied to the outside of the markings on the high side of the bridge deck cross slope.

2. The method for high-rutting-resistance bridge deck pavement for heavy traffic on urban expressways according to claim 1, characterized in that, In step (2), when the reduced-weight seal layer uses anionic emulsified asphalt synchronous crushed stone, the crushed stone adopts a zoned gradation design: 4.75-9.5mm limestone is laid in the wheel track zone; 4.75-7.2mm limestone is laid in the transition zone; and 2.36-4.75mm limestone is laid in the edge zone. The crushed stone embedment rate is >70%, forming a barbed structure. The asphalt application rate for the reduced-grade seal layer is controlled at 0.4 kg / m³. 2 -0.6kg / m 2 The asphalt is applied using a multi-stage spraying process: the first spraying applies 60% of the total amount and forms a film at 60°C; the second spraying applies the remaining 40% and reinforces the coating at 90°C.

3. The method for high-rutting-resistant bridge pavement for heavy traffic on urban expressways according to claim 1, characterized in that, In step (2), when the reduced-weight seal layer uses SBS modified asphalt synchronous crushed stone, the crushed stone adopts a compound particle size design: it is composed of 70wt% basalt with a particle size of 5-10mm and 30% limestone with a particle size of 2.36-4.75mm. Pre-coating with epoxy resin at 0.6%-0.8% of the total mass of crushed stone, with a crushed stone embedding rate >80%; The asphalt application rate for the reduced-grade seal layer is controlled at 0.4 kg / m³. 2 -0.6kg / m 2 The asphalt is sprayed at a high temperature of 165-175℃; the crushed stone is covered using a layered process: the first spraying covers 70% of the total crushed stone; the second spraying covers the remaining 30%.

4. The method for high-rutting-resistance bridge deck pavement for heavy traffic on urban expressways according to claim 1, characterized in that, In step (2), when the reduced material seal layer uses high viscosity modified asphalt synchronous crushed stone, the crushed stone is basalt with a single particle size of 6-10mm, and the polishing value of the basalt is ≥65. The crushed stone was pre-coated with 0.5% silane coupling agent, and the stone embedding rate was >75%. High-viscosity modified asphalt and embedded crushed stone form a barbed-sealing dual-effect layer; The asphalt application rate for the reduced-grade seal layer is controlled at 0.4 kg / m³. 2 -0.6kg / m 2 .

5. The method for high-rutting-resistance bridge pavement for heavy traffic on urban expressways according to claim 1, characterized in that, In step (3), the amount of asphalt in the modified asphalt mortar layer is 6.5%-7.0%; the gradation range of the mixture in the modified asphalt mortar layer is as follows: 100% passing through a 9.5mm sieve, 90%-100% passing through a 4.75mm sieve, 28%-50% passing through a 2.36mm sieve, 20%-36% passing through a 1.18mm sieve, 18%-26% passing through a 0.6mm sieve, 15%-22% passing through a 0.3mm sieve, 12%-18% passing through a 0.15mm sieve, and 8%-13% passing through a 0.075mm sieve.

6. The method for high-rutting-resistance bridge pavement for heavy traffic on urban expressways according to claim 1, characterized in that, The gradation ranges of the lower and upper bridge deck asphalt concrete pavement mixtures in step (3) are as follows: The asphalt content in the lower bridge deck asphalt concrete pavement mixture is 5.6%-5.8%; the passing rates of this mixture are as follows: 19mm sieve: 100%; 16mm sieve: 90-100%; 13.2mm sieve: 70%-85%; 9.5mm sieve: 50%-70%; 4.75mm sieve: 22%-35%; 2.36mm sieve: 17%-26%; 1.18mm sieve: 16%-24%; 0.6mm sieve: 14%-20%; 0.3mm sieve: 12%-17%; 0.15mm sieve: 12%-16%; 0.075mm sieve: 10%-12%. The asphalt content in the upper bridge deck asphalt concrete pavement mixture is 5.6%-5.8%. The passing rates of this mixture through a 19mm sieve are 100%, through a 16mm sieve is 90-100%, through a 13.2mm sieve is 65%-85%, through a 9.5mm sieve is 45%-65%, through a 4.75mm sieve is 20%-32%, through a 2.36mm sieve is 15%-24%, through a 1.18mm sieve is 14%-22%, through a 0.6mm sieve is 12%-18%, through a 0.3mm sieve is 10%-15%, through a 0.15mm sieve is 9%-14%, and through a 0.075mm sieve is 8%-12%.

7. The method for high-rutting-resistance bridge pavement for heavy traffic on urban expressways according to claim 1, characterized in that, The gradation ranges of the lower and upper asphalt concrete pavement mixtures in step (3) are as follows: The asphalt content in the lower bridge deck asphalt concrete pavement mixture is 5.9%-6.1%; the passing rates of this mixture are as follows: 19mm sieve: 100%; 16mm sieve: 100%; 13.2mm sieve: 90%-100%; 9.5mm sieve: 55%-75%; 4.75mm sieve: 22%-35%; 2.36mm sieve: 18%-28%; 1.18mm sieve: 16%-26%; 0.6mm sieve: 14%-22%; 0.3mm sieve: 12%-18%; 0.15mm sieve: 12%-17%; 0.075mm sieve: 10%-12%. The asphalt content in the upper bridge deck asphalt concrete pavement mixture is 5.9%-6.1%; the passing rates of this mixture are as follows: 19mm sieve: 100%; 16mm sieve: 100%; 13.2mm sieve: 90%-100%; 9.5mm sieve: 50%-75%; 4.75mm sieve: 20%-34%; 2.36mm sieve: 15%-26%; 1.18mm sieve: 14%-24%; 0.6mm sieve: 12%-20%; 0.3mm sieve: 10%-16%; 0.15mm sieve: 9%-15%; 0.075mm sieve: 8%-12%.

8. The method for high-rutting-resistance bridge pavement for heavy traffic on urban expressways according to claim 1, characterized in that, The waterborne epoxy asphalt in step (2) is compounded from epoxy resin emulsion and anionic emulsified asphalt at a mass ratio of 1:0.

8.

9. The method for high-rutting-resistance bridge pavement for heavy traffic on urban expressways according to claim 8, characterized in that, The anionic emulsified asphalt is sodium dodecyl sulfonate anionic emulsified asphalt; 5 wt% SBR latex and 3 wt% nano clay are added to the emulsified asphalt.

10. The method for high-rutting-resistance bridge pavement for heavy traffic on urban expressways according to claim 1, characterized in that, The SBS modified asphalt in step (2) uses 70# or 90# road petroleum asphalt as the base, and adds 4.2%-4.5% of star-shaped SBS modifier for shear modification. During the modification process, 2% of natural rock asphalt and 0.3% of sulfur are added as auxiliary modifiers, with a softening point ≥85℃. The high-viscosity modified asphalt uses TPE high-viscosity asphalt, with a viscosity of >50,000 Pa·s at 60℃ and a softening point ≥110℃.